Hypoglycemic Effect Determination of Soybean, Soybean Protein Fraction and Tempe in Diabetic Rats - Wulan, Siti Narsito; Astuti, Mary; Marsono, Y.; Noor, Zuheid (Fakultas Teknologi Pertanian Universitas Brawijaya, 2002)
Hypoglicemic effect of soybean, soybean protein fraction and tempe was determined in alloxan-induced diabetic rats. Blood glucose and urinary glucose level were measured to determine this effect.Soybean protein fraction had the highest hypoglicemic property. It lowered blood glucose level from 37.35 to 5.48 mg/dl/day/g carbohydrate consumed (85%). Tempe showed lower hypoglycemic effect than soybean protein fraction. Blood glucose level decreased 51%, from 31.57 to 15.59 mg/dl/day/g carbohydrate consumed. Soybean had the lowest hypoglycemic effect. It lowered blood glucose level from 47.47 to 27.70 mg/dl/day/g carbohydrate consumed (42%). Urinary glucose level had the same pattern as blood glucose level.Keywords : Hypoglicemic effect, blood glucose level, soybean, tempe